PERDAGANGAN KARET ALAM ANTARA NEGARA PRODUSEN UTAMA DENGAN AMERIKA SERIKAT - BONAR M. SINAGA; ELWAMENDRI - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
The result of reseach shows that expor supply of the main producer country tothe United States has the positive slope and inelactic toward price. Meanwhile thepalm plant was competitive plant for rubber plant. While, rubber production haspotential to increase the rubber expor of technical spesification. Rasio of Domesticrubber consumption with rubber expor of technical specification each of the mainprodicer country has potential to decrease ability rubber expor of tecnicalspecification.Rubber expor price of technical specification in main producer country in shortand long term was not resposive toward change of price in United State country.Impor demand the technical specification rubber United State has the negative slopeand inelactic toward price. The sinthetic rubber is substitute the natural rubber andincreasing the otomotive industry production and increasing the United Stateeconomy capcity tend to increase demand of technical natural rubbber in UnitedState.